Skin diseases among elderly patients attending skin clinic at the Regional Dermatology Training Centre, Northern Tanzania: a cross-sectional study. (December 2016) - Mponda, Kelvin; Masenga, John
Abstract Background As global population of the elderly continues to rise, a critical need to provide it with health services, including dermatology, will be significant, especially in developing countries like Tanzania. To adequately meet their dermatologic needs, knowledge of local patterns of skin conditions is vital. This study was aimed to describe the spectrum of skin diseases among elderly patients attending skin clinic at the Regional Dermatology Training Centre (RDTC) in Northern Tanzania. Methods A descriptive hospital based cross-sectional study was conducted between January 2013 and April 2013 at RDTC and included all patients aged 55 years and above who consented to be examined. Diagnoses were clinical, diagnostic tests being done only when necessary. Ethical clearance to conduct the study was granted. Results A total of 142 patients, age ranges 55–99 years, median age of 67.5 years were seen. Eczemas were the leading disease group (43.7 %), with unclassified eczemas (33.9 %) predominating. Papulosquamous disorders (15.4 %) were second with psoriasis (50 %) being the leading disease. Infections (11.3 % with fungal infections the leading group representing 5.6 % of all diseases), tumours (9.8 %: Kaposi's sarcoma 4.2 %), vascular disorders 9.1 % (lymphedema 4.9 %), autoimmune disorders 7.7 % (connective tissue diseases 4.9 %), vitiligo 4.2 %, nutritional diseases 2.1 % (pellagra 0.7 %), urticaria 0.7 % and drug reactions 0.7 %. Conclusions Eczemas are the most common group of disorders among elderly patients presenting at RDTC.